An examination of major works for wind band, and chamber ensemble: “Pantomime” by Pierre Mercure, “From chaos to the birth of a dancing star” by Allan Gordon Bell, and “Tafelmusik” by Godfrey Ridout - Stein, Edward Garret (Kansas State University, 2007)
This document was submitted to the Graduate School of Kansas State University in partial fulfillment for the Master’s in Music degree. It contains theoretical, historical, and rehearsal analyses for the Graduate Conducting Recital of Edward Garret Stein. The recital was performed by members of the Kansas State University Symphony Band in McCain Auditorium on Wednesday, March 13, 2007. The concert was intended to be an exploration of three important and diverse chamber works for winds. Selections included Pantomime by Pierre Mercure, Tafelmusik by Godfrey Ridout, and From Chaos to the Birth of a Dancing Star by Allan Gordon Bell. Employed in this report are the analytical methods based on the Blocher/Miles Unit Study from the Teaching Music through Performance in Band series as well as the Tracz concept of macro-micro score analysis.
Keywords: Analysis; Wind band; Chamber; Allan Gordon Bell; Pierre Mercure; Godfrey Ridout; Music (0413)